Influencia de las canciones infantiles en el desarrollo del lenguaje oral en los niños de 4 a 6 años del jardín de infantes María Guerrero Vásquez del cantón Chambo, provincia de Chimborazo durante el período 2010-2011. - Fiallos Ortiz, Mónica Elizabeth (2011)
The research deals with the influence of children's songs to enhance the oral language of children from 4 to 6 years of kindergarten Maria Guerrero Vasquez Chambo Canton, Chimborazo Province during the period 2010 to 2011. The research problem is knowing how to influence children's songs in oral language development. The objective of this study is to use nursery rhymes to make children develop the language effectively. As for the theoretical is based on psychological theories of learning, teaching and education. The research survey is analyzed by direct observation of teachers and children through tables and graphs important data was obtained, they were respectively analyzed and interpreted. The proposal raised concerns the development of a nursery rhyme CD recreational training for oral language development of children in order to provide a working tool for teachers to implement in their children and thus ensure the effective and efficient intellectual and oral pronunciation.